2022
DOI: 10.1002/anie.202203519
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Bonded α‐Fe2O3/Bi4MO8Cl Dot‐on‐Plate Z‐Scheme Junction with Strong Internal Electric Field for Selective Photo‐oxidation of Aromatic Alcohols

Abstract: Inferior contact interface and low charge transfer efficiency seriously restrict the performance of heterojunctions. Herein, chemically bonded α-Fe 2 O 3 / Bi 4 MO 8 Cl (M = Nb, Ta) dot-on-plate Z-scheme junctions with strong internal electric field are crafted by an in situ growth route. Experimental and theoretical results demonstrate that the internal electric field provides a powerful driving force for vectorial migration of photocharges between Bi 4 MO 8 Cl and α-Fe 2 O 3 , and the interfacial FeÀ O bond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…Therefore, enhancing interfacial interaction to establish a distinct charge transport channel can be an effective solution to this bottleneck. Recent studies have shown that the formation of interfacial chemical bonds can serve as an atomic-level charge transport channel, but it is subject to elemental composition in the utilized semiconductors. In comparison with chemical bond construction, enhancing intermolecular interaction through π–π conjugation , is well acknowledged to modulate the interfacial properties of organic semiconductors. , Owing to the unique electronic properties, the delocalized π-electrons are beneficial to carrier migration with small interface resistance. In addition, the driving force induced by the interfacial built-in electric field also plays a key role in carrier diffusion, which is determined by the asymmetric charge distribution due to the rearrangement of Fermi levels ( E F ). Advanced S-scheme carrier migration path exhibits superior interface dynamics to conventional type-II heterojunction. , However, the requirements of matched band structure and E F difference make the construction of S-scheme heterojunction challenging. Therefore, constructing superb 2D/2D S-scheme heterostructures with strong π–π conjugation and a giant built-in electric field at the interface is of great significance for boosting photoelectric response.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, enhancing interfacial interaction to establish a distinct charge transport channel can be an effective solution to this bottleneck. Recent studies have shown that the formation of interfacial chemical bonds can serve as an atomic-level charge transport channel, but it is subject to elemental composition in the utilized semiconductors. In comparison with chemical bond construction, enhancing intermolecular interaction through π–π conjugation , is well acknowledged to modulate the interfacial properties of organic semiconductors. , Owing to the unique electronic properties, the delocalized π-electrons are beneficial to carrier migration with small interface resistance. In addition, the driving force induced by the interfacial built-in electric field also plays a key role in carrier diffusion, which is determined by the asymmetric charge distribution due to the rearrangement of Fermi levels ( E F ). Advanced S-scheme carrier migration path exhibits superior interface dynamics to conventional type-II heterojunction. , However, the requirements of matched band structure and E F difference make the construction of S-scheme heterojunction challenging. Therefore, constructing superb 2D/2D S-scheme heterostructures with strong π–π conjugation and a giant built-in electric field at the interface is of great significance for boosting photoelectric response.…”
mentioning
confidence: 99%
“…The surface potential of the heterojunctions was imaged using in situ Kelvin-probe force microscopy (KPFM) to further investigate the reason for the striking improvement in photoelectric performance through the construction of heterojunctions. ,, As presented in Figure a–c, the heterojunction exhibits a more pronounced three-dimensional (3D) surface potential distribution in darkness compared to CuTCPP­(Cu) and CuTCPP­(Fe). As indicated by the line-scanning curves, the surface potentials of CuTCPP­(Cu), CuTCPP­(Fe), and the heterojunction were 33 mV, 29 mV, and 62 mV, respectively.…”
mentioning
confidence: 99%
“…It is widely reported that the ˙CH(OH)Ph radical, which can be induced by the interaction between BA and h + , is often considered the key intermediate for selective photo-oxidation of alcohol into aldehyde. 58,59 Therefore, butylated hydroxytoluene (BHT), a commonly used carbon-centered free radical trapping reagent, was added to verify whether ˙CH(OH)Ph radicals are involved in the photocatalytic process. 59 Clearly, both the conversion of BA and H 2 evolution remain, suggesting the simultaneous participation of electrons and holes for BZD and H 2 production instead of ˙CH(OH)Ph radicals.…”
Section: Resultsmentioning
confidence: 99%
“…58,59 Therefore, butylated hydroxytoluene (BHT), a commonly used carbon-centered free radical trapping reagent, was added to verify whether ˙CH(OH)Ph radicals are involved in the photocatalytic process. 59 Clearly, both the conversion of BA and H 2 evolution remain, suggesting the simultaneous participation of electrons and holes for BZD and H 2 production instead of ˙CH(OH)Ph radicals. Furthermore, the carbon-centered free radicals have been further explored by the in situ EPR measurements with 5,5-dimethyl-1-pyrroline N -oxide (DMPO) as the spin-trapping regent to gain more information on the radical intermediate mechanism of the reaction (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation